106 EDITH (EMERGENCY DEPARTMENT IN THE HOME): AN 18 MONTH AUDIT OF A NOVEL SERVICE. (18th November 2021) - Davis, A J; Delaney, A; Doyle, C; Sweeney, A; Kenny, L; Nally, S M; Namara, R M
Abstract: Background: The EDITH team has provided an alternative care pathway for older adults in need of emergency services. The traditional model, which involved the transport of an older adult to an emergency department has been replaced with emergency care that takes place in the persons' home. The EDITH service provides both medical and Occupational Therapy assessment and intervention in the home environment with onward referrals to appropriate agencies as indicated, thus negating the need for an emergency department presentation. Methods: Data from electronic patient records and OT logbooks were audited from the period 22/02/20 to 09/08/21. Data was gathered regarding attendances, outcomes and conveyance rates. Results: Since its' inception the EDITH service has treated 3, 137 patients. Following treatment, 2, 909 patients remained at home while 228 patients were transferred to hospital. This gives a conveyance rate of 7.2%. Three hundred and thirty six patients were referred to primary care or day hospital services. The average age of patients is 82 years and the average Manchester Triage category is priority 4. The EDITH service has saved the hospital 7.9 years of bed days (2, 909 bed days) as these patients have not presented to the emergency department. Conclusion: There is a growing body of evidence highlighting the detrimental impact a hospitalisation can have on an older adult (Mudge et al., 2019). There is a clear need for health care services to diversify in order to meet the needs of this ageing population. The EDITH service is leading this change in Irish healthcare by providing specialised emergency care and OT intervention for the older adult in their own homes. Reference: 1. Mudge et al. (2019). Hospital-Associated Complications of Older People: A Proposed Multicomponent Outcome for Acute Care. Journal of the American Geriatrics Society . 67(2).